Evaluation of mechanical properties of FDM components reinforced with fibre. Issue 1 (October 2021) - Rodríguez, P; Zapico, P; Robles, P E; Soto, A; Barreiro, J
Abstract: This research analyses the influence of different parameters of the Fused Deposition Modelling process with continuous carbon fibre reinforcement upon tensile strength of manufactured parts. For that, the appropriate behaviour of specimens designed according to ISO 527 standard was verified, in a preliminary test. Hereafter, a full factorial Design of Experiment was proposed with five parameters and two levels. After manufacturing and testing the specimens, a regression including all possible interactions of the parameters was performed with their tensile results. This model was optimized, considering the terms with the highest statistical significance (p-value less than 0.05), so that a simplified model of 14 terms with an r-squared of 97.5% was obtained. Thanks to this research the tensile response of a printed part as a function of the chosen manufacturing parameters can be predicted in advance.